Rapid Screening of Active Components with Topoisomerase I Inhibitory Activity in Sophora alopecuroides L. Based on Ultrafiltration Coupled with UPLC-QTOF-MS - Zhang, Lin; Yin, Xiaoying; Wan, Xi; Sun, Yun; Cao, Menghui; Ouyang, Sheng (Current Pharmaceutical Biotechnology, 2022)
Background: Topoisomerase I (Topo I) is a key target of many antitumor drugs in vivo. Alkaloids in Sophora alopecuroides L. can reportedly inhibit Topo I activity, but the pharmacodynamic material basis has not yet been determined. Objective: This study aimed to rapidly identify active components which inhibit Topo I in S. alopecuroides L. Methods: Affinity ultrafiltration coupled with ultra-performance liquid chromatography-quadrupole time of flight-mass spectrometry (UF-UPLC-QTOF-MS) screening system based on Topo I protein was established to screen and isolate a total alkaloid fraction in S. alopecuroides L. Topo I inhibitory activity and anti-tumor proliferation activity of the screened components were evaluated, and their molecular mechanisms were studied. Results: Six compounds that bound specifically to Topo I were obtained. Further screening showed that matrine, cytisine, and sophoridine presented higher inhibitory activity on Topo I and were able to inhibit the proliferation of breast cancer MDA-MB-468 cells with IC50 values of 9.40 ± 1.12 mM, 17.4 ± 2.20 mM, and 10.4 ± 1.37 mM, respectively. To the best of our knowledge, their dual molecular mechanisms against Topo I have not discussed to date. In this study, the following dual mechanisms are reviewed for the first time: (1) stabilization of the Topo I-DNA complex and (2) inhibition or blocking of Topo I binding to DNA. Conclusion: Matrine, cytisine, and sophoridine from S. alopecuroides L. were defined as the active components possessing Topo I inhibitory activity, and their pharmacological mechanism was confirmed, which provided an important base for further research and development of antitumor components from S. alopecuroides L.
Keywords: Sophora alopecuroides L